2009
DOI: 10.1002/jnr.22223
|View full text |Cite
|
Sign up to set email alerts
|

Matrigel supports survival and neuronal differentiation of grafted embryonic stem cell‐derived neural precursor cells

Abstract: Cell replacement therapy holds great promise as a means of treating neurological disorders, including Parkinson's disease. However, one of the major obstacles to the success of this treatment is the low survival rate of grafted cells, which probably results from mechanical damage, acute inflammation, and immunological rejection. To overcome this problem, we investigated the effect of different types of extracellular matrix (ECM) on the survival and differentiation of embryonic stem (ES) cell-derived neural pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 42 publications
3
128
0
Order By: Relevance
“…The Matrigel assay is commonly considered to be an experimental method that measures the ability of cells to promote angiogenesis in vitro [15] and is also used to support the differentiation of neural precursor cells into neuronal cells [16] . NGF is a common neurotrophic factor, so we needed to exclude the possibility that MSCs normally have the ability to differentiate into neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Matrigel assay is commonly considered to be an experimental method that measures the ability of cells to promote angiogenesis in vitro [15] and is also used to support the differentiation of neural precursor cells into neuronal cells [16] . NGF is a common neurotrophic factor, so we needed to exclude the possibility that MSCs normally have the ability to differentiate into neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that tubes formed in Matrigel may differentiate into endothelial cells. Because the Matrigel can also support neuronal differentiation of neural precursor cells [16] , we examined whether the MSCs differentiated into neurocytes. MSCs were positively expressing early neuronal markers and some mature neuronal markers.…”
Section: Mscs Cultured In Matrigel May Differentiate Into Endothelialmentioning
confidence: 99%
“…One natural hydrogel used for cell delivery is Matrigel™, a material derived from a mouse sarcoma cell line primarily composed of laminin-1 and collagen IV and containing many adhesive molecules and growth factors that promote cell viability. Transplantation of mouse ESC-derived NPCs in Matrigel™ into the striatum resulted in a larger graft volume and increased the number of tyrosine hydroxylase-positive dopaminergic neurons (Uemura et al, 2010). Unfortunately, as Matrigel™ is derived from a xenobiotic source, it has high batch-to-batch variability and is unsuitable for clinical use (Jin et al, 2010).…”
Section: Biomaterials For Cell Therapymentioning
confidence: 99%
“…MatrigelBD is a solubilized basement membrane extracted from Engelbreth-HolmSwarm (EHS) mouse sarcoma (Hughes et al, 2010). In preliminary studies, MatrigelBD has been used in cardiomyocyte progenitor transplantation experiments, in a cardiac infarction animal model, and to promote in vivo angiogenesis (Ou et al, 2011;Bhat et al, 2012), and stimulates embryonic stem cells (ESC) to survive and differentiate in vitro (Uemura et al, 2010). One report showed that dental pulp stem cells (DPSC) co-cultured within MatrigelBD maintained their osteogenic differentiation potential, suggesting possible applications for use in skeletal defects (van Gastel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%